DETERMINANTS OF TRANSMISSION COVID-19 IN SOUTH SULAWESI - Masriadi Masriadi; Nur Ulmy Mahmud; Nazli Javid; Muhammad Sarwin; Lukman; Sitti Hutami Megantari; Ayu Angraeni Suprianti (Universitas Airlangga, 2022)
Background: Corona Virus (COVID-19) is a new respiratory viral infectious disease that can cause illnesses ranging from the common cold to severe acute respiratory syndrome. Subsequently, as of May 31, 2022, the government of South Sulawesi reported 143,276 confirmed cases, 2,463 deaths, and 140,395 recovered patients. Purpose: To analyze the impact of behavior, travel history, and comorbidities on the incidence of COVID-19 in South Sulawesi. Methods: This is observational research with a cross-sectional study design and was conducted from January-April 2022 in 7 districts of South Sulawesi Province. A population of 650 respondents with a total sample of 161 patients confirmed positive and 189 suspected of having COVID-19. The Chi-square test and multiple logistic regression were used to analyze the data. Results: There was a relationship between travel history (p0.00; OR 2.19), knowledge (p0.03; OR 1.74), and actions (p0.00; OR 0.18) on the incidence of COVID-19. Additionally, no relationship was reported between comorbidities (p0.85), attitudes (p0.90), and level of knowledge (p0.08>(0.05) on the incidence of COVID-19. The most influential variable in the rapid spread was travel history, with an exp(B) value of 2.19 CI (95%) (LL=1.26; UL=3.80). Conclusion: The results showed that travel history, knowledge, and actions made a major contribution to the spread of COVID-19 in South Sulawesi Province.